Penyesuaian Krisis Global dengan Faktor-Faktor Produksi dan Pendapatan Petani Plasma PIR Kelapa Sawit - Elisa Wildayana; Imron Zahri; Andy Mulyana; Laila Husin (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2016)
Wildayana et al, 2016.Â Matching Global Crises with Application of Production Factors and Income of NES Oil Palm Plasma Farmers. JLSO 5(1):10-17.The research aimed to analyze the global crisis adjustment to the production factors and income of NES oil palm smallholder. The research location is located in swamp land Talang Sepucuk, OKI District (PIR Trans) and PIR Bun is sited in Betung Banyuasin, South Sumatra. The research method was a field survey using a questionnaire to smallholders. Collected data are statistically processed with SPSS version 21. The research concludes that the global crisis has led to a very significant reduction in the use of fertilizers and pesticides and the significant differences in the utilization of manpower. The use alsintan showed no significant difference. Very sharp reduction has occurred in PIR Bun compared to PIR Trans smallholder farmers. As a result of the global crisis, the PIR Trans smallholder incomes decreased by 25.76% and PIR Bun decreased by 36.95% and vary significantly due to the global crisis. But the distribution of smallholder incomes do not show the proportion of the difference.